Tinjauan Literatur : Potensi Senyawa Bioaktif Senggugu (Clerodendrum Serratum) sebagai Tanaman Obat Tradisional - Ihsan Alfi Andri; Vriezka Mierza (Poltekkes Kemenkes Padang, 2025)
This study aims to explore in depth the potential of bioactive compounds contained in the Senggugu plant (Clerodendrum serratum) as a traditional medicinal plant useful in traditional medicine. This research is a systematic review of the literature with data search using PubMed and Google Scholar databases. Inclusion criteria included research related to Clerodendrum serratum, research articles, and published in the last 10 years. From the initial search results of 61 articles, 8 relevant articles were selected for further analysis and it was found that various parts of the plant, especially roots and leaves, contain active compounds such as ursolic acid, flavonoids, saponins, and silver nanoparticles, which exhibit significant anti-inflammatory, antioxidant, antimicrobial, and antarthritic properties. Laboratory and in silico studies support the effectiveness of the compound in inhibiting the activity of inflammatory enzymes and proinflammatory cytokines, such as COX-2 and TNF-α, which are involved in inflammatory processes and other chronic diseases. This therapeutic potential suggests that Senggugu can be a safe and natural alternative in the treatment of various diseases, while supporting efforts to utilize local plant resources to improve public health.